The Smac Mimetic BV6 Improves NK Cell-Mediated Killing of Rhabdomyosarcoma Cells by Simultaneously Targeting Tumor and Effector Cells - Fischer, Kyra; Tognarelli, Sara; Roesler, Stefanie; Boedicker, Cathinka; Schubert, Ralf; Steinle, Alexander; Klingebiel, Thomas; Bader, Peter; Fulda, Simone; Ullrich, Evelyn (Frontiers in Immunology, 2017)
Rhabdomyosarcoma (RMS), the most common cancer of connective tissues in pediatrics, is often resistant to conventional therapies. One underlying mechanism of this resistance is the overexpression of inhibitor of apoptosis (IAP) proteins, leading to a dysfunctional cell death program within tumor cells. Smac mimetics (SM) are small molecules that can reactivate the cell death program by antagonizing IAP proteins and therefore compensating their overexpression. Here, we report that SM sensitize two RMS cell lines (RD and RH30) towards natural killer (NK) cell-mediated killing on the one hand, and increase the cytotoxic potential of NK cells on the other. The SM-induced sensitization of RH30 cells towards NK cell mediated killing is significantly reduced through blocking TRAIL on NK cells prior to coculture. In addition, the presence of zVAD.fmk, a pan caspase inhibitor, rescues tumor cells from the increase in killing, indicating an apoptosis dependent cell death. On the NK cell side, the presence of SM in addition to IL-2 during the ex vivo expansion leads to an increase in their cytotoxic activity against RH30 cells. This effect is mainly TNF-dependent and partially mediated by NK cell activation, which is associated with transcriptional upregulation of NF-kB target genes such as IkBa and RelB. Taken together, our findings implicate that SM represent a novel double hit strategy, sensitizing tumor and activating NK cells with one single drug.